ProSAAS-Derived Peptides are Colocalized with Neuropeptide Y and Function as Neuropeptides in the Regulation of Food Intake - Wardman, Jonathan H. (Public Library of Science, 2011)
ProSAAS is the precursor of a number of peptides that have been proposed to function as neuropeptides. Because proSAAS mRNA is highly expressed in the arcuate nucleus of the hypothalamus, we examined the cellular localization of several proSAAS-derived peptides in the mouse hypothalamus and found that they generally colocalized with neuropeptide Y (NPY), but not α-melanocyte stimulating hormone. However, unlike proNPY mRNA, which is upregulated by food deprivation in the mediobasal hypothalamus, neither proSAAS mRNA nor proSAAS-derived peptides were significantly altered by 1–2 days of food deprivation in wild-type mice. Furthermore, while proSAAS mRNA levels in the mediobasal hypothalamus were significantly lower in Cpe(fat/fat) mice as compared to wild-type littermates, proNPY mRNA levels in the mediobasal hypothalamus and in other subregions of the hypothalamus were not significantly different between wild-type and Cpe(fat/fat) mice. Intracerebroventricular injections of antibodies to two proSAAS-derived peptides (big LEN and PEN) significantly reduced food intake in fasted mice, while injections of antibodies to two other proSAAS-derived peptides (little LEN and little SAAS) did not. Whole-cell patch clamp recordings of parvocellular neurons in the hypothalamic paraventricular nucleus, a target of arcuate NPY projections, showed that big LEN produced a rapid and reversible inhibition of synaptic glutamate release that was spike independent and abolished by blocking postsynaptic G protein activity, suggesting the involvement of a postsynaptic G protein-coupled receptor and the release of a retrograde synaptic messenger. Taken together with previous studies, these findings support a role for proSAAS-derived peptides such as big LEN as neuropeptides regulating food intake.